Q-Switched Fiber Laser by Using Spider Web as Saturable Absorber - ONG, ONG KAH YONG; Noor Ummi Hazirah Hani Zalkepali (Enhanced Knowledge in Sciences and Technology, 2024)
Exploring new saturable absorber (SA) materials with excellent performance to achieve Q-switching operations is a hot topic in laser research. For SA, there are fews techniques to produce Q-switched fiber laser including using a real SA like a semiconductor saturable absorber mirror (SESAM) or an artificial SA like a nonlinear polarisation rotation (NPR), nonlinear optical loop mirror (NOLM), or a nonlinear amplifying loop mirror (NALM). However, there are some drawbacks such as substantial intensity losses, a small operating wavelength, and challenges in optical preparation according to these techniques, therefore, spider web is using as potential SA in this study since the characteristic of spider silk is stronger strength and biocompability. According to the result obtained for spider silk, the modulation depth and saturation intensity was 20.67% and 0.11 MW/cm2 for spider silk. It was also found that the repetition rate raised from 23.3 to 63.3 kHz, while the pulse width has been reduced from 9.173 to 3.889 µs by using laser diode. The signal-to-noise ratio (SNR) for the fundamental frequency is determined to be 63.3 kHz which is calculated to be 56.21 decibels (dB). The highest average output power and pulse energy is 0.074 mW and 1.162 nJ respectively. As a result, the result of the spider silk can be considered as a alternative SA for generation of pulse fiber laser.